Alat Penyiram Tanaman Otomatis Berbasis Arduino Menggunakan Internet Of Things (IOT) - Azzaky, Nabil; Widiantoro, Anang (Universitas Hang Tuah, 2020)
Plants are living things that are important for the needs of human life. The benefits of plants for humans are as an air purifier. Water is needed for plants to grow. Besides being used in the process of photosynthesis, water is also used by plants to dissolve minerals that are absorbed by the roots from the soil as a process of developing the plants. Watering can maintain and care for plants to grow and develop. The purpose of this study is to create a tool that can water plants using Android devices by utilizing an internet connection for control and monitoring. By using smartphone android that has been installed the blynk application can communicate with Arduino using an enhancement in the form of ESP8266 so that it can be connected via a WIFI connection so that it allows the user to control and monitor the plant sprinklers, by working sending commands on and off through blynk and receiving data the temperature and humidity obtained from the DHT22 sensor. The results of this study, the watering plant can work well, can control watering manually and automatically. The tool will water the plants when the temperature is more than 31 Â° C